Progress in Nanotechnology 2009
DOI: 10.1002/9780470588246.ch41
|View full text |Cite
|
Sign up to set email alerts
|

(Na0.8K0.2)0.5Bi0.5TiO3Nanowires: Low‐Temperature Sol–Gel–Hydrothermal Synthesis and Densification

Abstract: The sol-gel-bydrothermal processing of (Nao.sKo.z)o.sBio.s Ti03 (NKBT) nanowires as weU as their densification behavior were investigated. The morphology and structure analyses indicated that the sol-gel-bydrothermal route led to the formation of phase-pure perovskite NKBT nanowires with diameters of 50-80 nm and lengths of 1.5-2 Jim, and the processing temperature was as low as 160°C, but the conventional sol-gel route tended to lead to the formation of NKBT agglomerated porous structured nanopowders, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…While much effort has been focused on the investigation of piezoceramics, increasing attention has been paid to the development of one‐dimensional (1D) piezoelectrics, e.g., nanorod, nanowire, nanotube, etc., which may be utilized in the fields of nanoelectromechanical system (NEMS), energy harvesting devices, photocatalysis, so on . In the case of piezoelectric materials, a wide variety of materials including ZnO, BaTiO 3 , PZT, etc.…”
Section: Promising Applications For Transducers and Energy Harvestingmentioning
confidence: 99%
“…While much effort has been focused on the investigation of piezoceramics, increasing attention has been paid to the development of one‐dimensional (1D) piezoelectrics, e.g., nanorod, nanowire, nanotube, etc., which may be utilized in the fields of nanoelectromechanical system (NEMS), energy harvesting devices, photocatalysis, so on . In the case of piezoelectric materials, a wide variety of materials including ZnO, BaTiO 3 , PZT, etc.…”
Section: Promising Applications For Transducers and Energy Harvestingmentioning
confidence: 99%
“…Besides, traces of the cube crystals are found in the NBT ceramics sintered from cubes, indicating that the crystal morphology has an influence on the microstructure of ceramics. Hou et al reported that the morphologies of precursors had an effect on mass and energy transition during the sintering process, which could affect the density and the electrical properties of sintered ceramics …”
Section: Resultsmentioning
confidence: 99%
“…While for sol–gel‐hydrothermal process, it is supposed that chained nanoclusters with a well‐defined morphology are formed during the gelation of BNdT sol, by controlling the hydrolysis of the sol. These chained nanoclusters could serve as the nuclei of BNdT during hydrothermal treatment . “Dissolution–crystallization” has been considered to be a basic mechanism to describe the hydrothermal process .…”
Section: Resultsmentioning
confidence: 99%
“…However, these chemical methods still need an additional calcined process at a temperature of >400°C, which is far from low cost and result in agglomeration, inhomogeneous particle size, and the Bi volatilization of Bi 4 Ti 3 O 12 powders. As a novel method to prepare oxide powders under mild temperatures, the sol–gel‐hydrothermal technique has the double advantage of both sol–gel and hydrothermal synthesis, such as high degree of crystallinity, well‐controlled morphology, and narrow particle size distribution of powders, etc …”
Section: Introductionmentioning
confidence: 99%